Tax Avoidance Sebagai Latar Belakang Dalam Memanfaatkan Tax Deductible Expense (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI) - Fitri Oktariani; Putu Indrajaya Lembut (InFestasi, 2018)
This study aims to test and prove empirically the effect of tax avoidance on the cost of debt. The research population is a company listed on the Indonesia Stock Exchange with a sample of companies in the manufacturing category during 2012 to 2017, which is as many as 50 sample companies. Sampling uses purposive sampling and the data analysis method used is a simple linear regression method. The results of this study prove that tax avoidance has a positive effect on the cost of debt. Based on the results of testing this study, it can be concluded that the company will always use a tax deductible expense in its efforts to conduct tax avoidance regardless of the tax rate that has been imposed by the government.Thus, the government should consider further policies by focusing more on regulating the recognition of tax deductible expenses, rather than issuing a policy of reducing back rates, especially for corporate taxpayers.